Fertilizantes foliares e regulador de crescimento no manejo da mancha aureolada do cafeeiro - Resende, Alexandre Ribeiro Maia de (2018)
Coffee cultivation is an important agricultural activity in Brazil. However, several factors can cause losses in the productivity of this crop, among which the diseases stand out. The growing demand for alternatives in the management of plant diseases aims to reduce the use of fungicides with the use of foliar fertilizers, for example. Thus, this study aims to evaluate the effect of foliar fertilizers on the management of coffee bacterial blight spot. A formulation of manganese phosphite (FMn; Phytogard Mn ® , 30% P2O5 and 9% Mn; 3.5 mL.L -1 ) associated with a macro-micronutrient leaf fertilizer (Fmm; Dacafé Cerrado ® ; 10% N, 4% S, B, 5% Fe and 5% Zn; 7.5 mL.L -1 ); FMn + Fmm + growth regulator (Sm; Stimulate ® ; 0.009% Cytokinin; 0.005% Gibberellin; 0.005% indolebutyric acid); Fn + Fmm + Sm + cobalt and molybdenum leaf fertilizer (Fcm; Hold ® , 2% Co and 3% Mo, 2.5 mL.L -1 ) and a control treatment without application. The severity and incidence of coffee bacterial blight spot, macro and micronutrient content, liquid photosynthetic rate (TFL), phenylalanine ammonialyase (PAL) enzyme activity, lignin content and ethylene synthesis were evaluated. All treatments significantly reduced the area under severity disease progress curve (AUSDPC) of the coffee bacterial blight spot and promoted control from 63 to 71%. There was no significant difference between the treatments and the control for the area under incidence disease progres curve (AUIDPC). All treatments promoted significant increases in the levels of phosphorus (P) and sulfur (S). Regarding the micronutrients, a significant difference was observed between the treatments and the control for nutrients boron (B), manganese (Mn) and zinc (Zn). All treatments provided a significant increase in the net photosynthetic rate in relation to the control. All treatments significantly inhibited the ethylene synthesis in the seedlings when compared to the control. There was inhibition of 54 to 76% in the synthesis of this hormone. There was no significant difference between the treatments and the control for the PAL activity and the soluble lignin content. The foliar fertilizers tested have potential for the management of the coffee bacterial blight spot.